2022
DOI: 10.1111/jth.15576
|View full text |Cite
|
Sign up to set email alerts
|

Structurally abnormal collagen fibrils in abdominal aortic aneurysm resist platelet adhesion

Abstract: Background: Platelet adhesion to the subendothelial collagen fibrils is one of the first steps in hemostasis. Understanding how structural perturbations in the collagen fibril affect platelet adhesion can provide novel insights into disruption of hemostasis in various diseases. We have recently identified the presence of abnormal collagen fibrils with compromised D-periodic banding in the extracellular matrix remodeling present in abdominal aortic aneurysms (AAA).Objective: In this study, we employed multimoda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Besides, mechanical damages to connective tissues can also render the collagen triple-helix in a denatured state. Our understanding of the biological significance of collagen denaturation in disease and injury is still in its infancy, although evidence for the presence and disease-correlation of denatured collagen is emerging from dozens of recent studies enabled by the CHP-collagen hybridization (Table ).…”
Section: Biology Of Collagen Hybridizationmentioning
confidence: 99%
“…Besides, mechanical damages to connective tissues can also render the collagen triple-helix in a denatured state. Our understanding of the biological significance of collagen denaturation in disease and injury is still in its infancy, although evidence for the presence and disease-correlation of denatured collagen is emerging from dozens of recent studies enabled by the CHP-collagen hybridization (Table ).…”
Section: Biology Of Collagen Hybridizationmentioning
confidence: 99%
“…However, whether platelet transfusion can be used as a therapy for the repair of rAAA is still controversial [ 71 ]. Jones et al reported that platelet adhesion is mainly restricted to areas composed of normal collagen fibers instead of the abnormal ones [ 72 ]. The collagen fibril structure is likely to be normal in the early (compared to advanced) stage of AAA, which may explain why in one report, diminished platelet adhesiveness in AAA remained abnormal even after transfusion of normal blood [ 73 ].…”
Section: The Role Of Platelets In Aaa Progressionmentioning
confidence: 99%